THE IMPORTANCE OF FORMING LITERARY CONCEPTS IN PRIMARY SCHOOLS (Conference Zone, 2022)
In primary education, the main task of the educator is to enrich the creative imagination of the student. This article discusses the importance of forming literary concepts in students in elementary school reading lessons.